Penerapan Model Pembelajaran Berbasis Masalah Guna Peningkatan Pengetahuan di SMA Negeri 3 Kota Semarang - Saputra, Iwan; Santoso, Apik Budi; Aji, Ananto; Sanjoto, Tjaturrahono Budi; Suharini, Erni (Ideas Publishing, 2024)
Effective learning can be observed through the effectiveness of the teaching process itself. The aim of this study is to analyze the implementation and effectiveness of the problem-based learning model and its impact on improving students' knowledge. This research employs a quantitative method. The problem-based learning model follows five stages. The results of the study indicate that the N-Gain score, used to measure the effectiveness of the learning model, reached 98%, indicating that it is effective when applied in problem-based learning assisted by the ArcGIS Story Map. Additionally, students' responses showed a score of 70.85, which is categorized as very good. Furthermore, the post-test scores were higher than the pre-test scores, demonstrating an improvement in students' knowledge.